Influences of pipe–soil interaction on dynamic behaviour of deepwater S-lay pipeline under random sea states. (3rd April 2017) - Gong, Shunfeng; Xu, Pu
ABSTRACT: The pipe–soil interactions have an important influence on the dynamic behaviour of offshore pipelines in the touchdown zone (TDZ) during deepwater S-lay. This paper mainly aims to reveal the dynamic behaviour of the pipeline in the TDZ, and its actual dynamic lay effects. A full finite element model for deepwater S-lay systems is primarily developed to simulate the dynamic responses of offshore pipeline from the pipelay vessel via the stinger to the seabed, in which pipelay vessel motions, pipeline hydrodynamics, clashing contacts between the pipeline and the stinger rollers and pipe–seabed interactions are considered particularly. The numerical analysis of an illustrative case for a gas export pipeline being installed to a water depth of 1500 m in the South China Sea is carried out in the time domain using the commercial computer code OrcaFlex. The influences of seabed soil models, soil characteristics, submerged self-weight of the pipe, surface waves, and pipelay vessel motions on the dynamic behaviour of the pipeline in the TDZ have been quantitatively studied in view of non-linear hysteretic soil model. The results indicate that the soil characteristics and the pipelay vessel motions induced by the surface wave have great influence on the bending moment and embedment of the pipeline, and the seabed resistance.